Education policy as a roadmap for achieving the sustainable development goals : effecting a paradigm shift for peace and prosperity through new partnerships - Taysum, Alison (Bingley, U.K. : Emerald Publishing Limited, 2019)
The 17 Sustainable Development Goals (SDGs) have been agreed globally as an unprecedented, ambitious and innovative agenda for prosperity and peace for people and the planet. Currently researchers, policymakers and nations are trying to identify clear routes for achieving these ambitious goals by 2030. This timely text examines how education policy provides a roadmap to achieving Sustainable Development Goal 4, achieving inclusive and equitable quality education and promoting lifelong learning opportunities for all. Taysum situates the SDGs, and the roadmap to achieving them, within a historical framework of established philosophy by drawing upon the ideas of the social contract, moral values and universal principles. As well as offering a theoretical understanding of these concepts, this research also offers practical solutions by demonstrating how university Vice Chancellors, Deans of Faculties and Schools of Education can work in partnership with the wider community in order to achieve the SDGs. Supported by a website and rich bank of practical resources, this book will prove invaluable for education leaders and those in the fields of higher education and moral philosophy.
Chapter 1. To rationalise apriori or not to rationalise apriori is that an empirical question? -- Chapter 2. The Policy context: challenging the crisis of contemporary culture and popularism with ABCDE to achieve SDG 4 -- Chapter 3. Assessment for Personal and social learning: a Deweyan perspective for education, and inclusion -- Chapter 4. Creating democratic identities for a social contract -- Chapter 5. Replacing the hierarchical master in a social contract with autonomous citizens actively participating within the force of the common whole -- Chapter 6. Educational leaders using ABCDE to explore human behaviours in social contracts in relation to embedded and disembedded economies -- Chapter 7. Groundwork case study of universities building capacity for education, inclusion and philosophies of trust through doctoral study: the literature and methodologies -- Chapter 8. Case studies of higher education building capacity for education, inclusion, identity and philosophies of trust through the doctorate: the findings -- Chapter 9. A masters 'Level 7 EQF' training course to deliver ABCDE through APSL to EYSIER -- Chapter 10. Step by step application of a blueprint for character development for evolution (ABCDE) and A framework for assessment for learning and progress towards sustainable development goals -- Chapter 11. To rationalise apriori or not to rationalise apriori: is that an empirical question? -- Chapter 12. Conclusions to education policy as a road map for achieving the sustainable development goals -- Professional educators and administrators' committees for empowerment (PEACE) -- Index.
Includes index.
Print version record.
Keywords: Sustainable development; Education and state; Business & Economics -- Development -- Sustainable Development; Economic history